The Effect of Household Waste Reduction on the Lifespan of Parit Enam Landfill in Pangkalpinang City: Using Dynamic System Modeling - Hadi Fitriansyah; Maryono Maryono (Universitas Diponegoro, 2021)
Currently, there are still problems occurring in waste management activities in Pangkalpinang City. Solid waste that is scattered in the City of Pangkalpinang is caused by waste that has not been transported and handled. TPA Parit Enam's capacity, which serves solid waste in Pangkalpinang City, will decrease every year due to an overload of incoming waste generation. Currently, the City of Pangkalpinang aggressively implements a waste management policy at the source or the 3R program, including waste bank activities and waste processing at reduce, reuse and recycle (3R) landfills. The purpose of this study was to determine the effect of household waste reduction activities on the current use of the Parit Enam landfill in Pangkalpinang City in each of the scenarios that were compiled. The compilation model uses Powersim Studio 2005. The dynamic analysis shows that the activities that follow the waste at the source and respect what happens in TPS 3R Pangkalpinang City can affect TPA Parit Enam's useful life and produce a suitable scenario to be applied in the waste management activities of Pangkalpinang City. Scenario C (Optimistic), the valuable life of Parit Enam Landfillreaches 2023, and scenario C (Optimistic) can reduce the amount of waste transported by 29.65% compared to scenario A (Business as Usual). Besides, the proportion of household waste reduction reached 48% at the end of the simulation year.